Modelamiento de la formación de scale del agua de producción del Campo Castilla (2012)
This work contains the modeling of the formation of water scale production Castilla Field, located in the Llanos Basin. First define the specific field conditions, its location, the formations present, their stratigraphy and petrophysical properties. It identifies all the specifications of the composition of produced water, such as physical and chemical properties, defining their older compounds such as chlorine, calcium, sulphates etc., and less as the Oxygen, Carbon Dioxide and so on. The efect of mixing them in the formation of scale and what are the factors that infuence such as temperature, acidity, pressure, pH, and alkalinity. The combination of the above variables results in the formation of fouling best known as those of calcium carbonate, calcium sulfate and strontium sulfate. The ion distribution schemes show in detail the wells of interest, producing formations and concentrations of individual components.